Dependency Injection Principles, Practices, and Patterns - Van Deursen, Steven; Seemann, Mark (Manning Publications, 2019)
Dependency Injection Principles, Practices, and Patterns is a revised and expanded edition of the bestselling classic Dependency Injection in .NET . It teaches you DI from the ground up, featuring relevant examples, patterns, and anti-patterns for creating loosely coupled, well-structured applications. The well-annotated code and diagrams use C# examples to illustrate principles that work flawlessly with modern object-oriented languages and DI libraries.
Keywords: Microsoft .NET Framework; Object-oriented programming (Computer science); Programmation orientée objet (Informatique)